Biodiversities and Abundanece of Plankton and Benthos in Lake Jempang, West Kutai - Ghitarina Ghitarina; Deni Udayana; Henny Pagoray (Journal of Wetlands Environmental Management, 2018)
The discharge of pollutants which is derived from industrial waste, such as oil and gas, palm oil, coal mining, and domestic activities, Â into the Mahakam river basin may contribute to the declining of water quaity of Mahakam river basin including Lake Jempang in West Kutai Regency. The aim of this study was to identify the condition of plankton and benthos in Lake Jempang, The study was conducted through survey, observation, and measurement of plankton and benthos communities. The results showed that the abundance, diversity, equitability and the dominance indexes of plankton and benthos are still relatively moderate.Â Â